Women, Subalternity, and the Historical Novel of María Rosa Lojo - Kathryn Lehman (Studies in 20th & 21st Century Literature, 2005)
María Rosa Lojo (1954) has received critical recognition as a poet, short-story writer, and novelist. Her poetic work Visiones (1984) and Forma oculta del mundo (1991), first book of short-stories Marginales (1986), and two novels Canción perdida en Buenos Aires al Oeste (1987) and La pasión de los nómades (1994), have received prestigious awards. Lojo's most recent work, informed and inspired by archival sources, has been acclaimed by both critics and the general public for having radically altered the established representation of canonical historical figures. The novels La princesa federal (1998), and Una mujer de fin de siglo (1999), and the short stories in Historias ocultas en la Recoleta (2000) and Amores insólitos de nuestra historia (2001), have proven to be a commercial success, indicative of the wider international phenomenon in which women are at the centre of both revisionist historiography and the new historical novel, as writers and as subjects, an important challenge to the traditional gendering of history. The marketing of this revisionist work has sparked a backlash against these forms of new historical writing. Kathryn Lehman asked Lojo to comment on the current position of women's writing and the historical novel in Argentina in an interview in Buenos Aires in October 2000 and again in September of 2002.
Keywords: María Rosa Lojo; canonical historical figures; women; historical novel; women& #x27; s writing; subalternity; review; literature review